How Do Banks and Households Manage Interest Rate Risk? Evidence from the Swiss Mortgage Market - Christoph Basten; Benjamin Guin; Cathérine Tahmee Koch (Center for Economic Studies and ifo Institute (CESifo), 2017)
We exploit a unique data set that features both un-intermediated mortgage requests and independent offers from multiple banks for each request. We show that households typically are not prudent risk managers but prioritize the minimization of current mortgage payments over the risk of possible hikes in future mortgage payments. We also provide evidence that banks do influence the contracted mortgage rate fixation periods, trading off their own exposure to interest rate risk against the borrowers' affordability and credit risk. Our results challenge the implicit assumption of the existing mortgage choice literature whereby fixation periods are determined entirely by households.
Keywords: D12; E43; G21; 330; Fixed-Rate Mortgage (FRM); Adjustable-Rate Mortgage (ARM); fixation period; maturity mismatch; interest rate risk; credit risk; duration